Diverse reactivity of NOBF4 towards silylene, disilene, germylene and stannylene - Parvin, Nasrina; Sen, Nilanjana; Muhasina, Puthan Veetil; Tothadi, Srinu; Parameswaran, Pattiyil; Khan, Shabana (Chemical Communications, 2021)
{The reactivity of NOBF4 towards silylene, disilene, germylene, stannylenes has been described. Smooth syntheses of compounds of composition [PhC(NtBu)(2)E(= O -> BF3)N(SiMe3)(2)